Revolutionizing Payment Trends: Balipay E-Wallet Technology Acceptance with Trust Mediation - Melianthi, Ni Kadek Indah; Darma, Gede Sri (Jurnal Aplikasi Manajemen, 2024)
The trend towards a cashless society in Indonesia is rapidly advancing, driven by the introduction of Bank BPD Bali's innovative e-wallet, Balipay. However, the bank faces significant challenges amidst escalating competition from other e-wallet products. This research addresses these challenges by examining the factors influencing users' interest in adopting and using Balipay. Utilizing the Technology Acceptance Model (TAM), the study considers perceived usefulness, perceived ease of use, and additional constructs related to perceived security and trust regarding the Balipay e-wallet. Data for the research was collected through an online survey involving 180 active Balipay users in Bali, and the analysis was conducted using Structural Equation Modeling (SEM) through the SmartPLS 4 tool. The findings indicate that perceived usefulness has a significant and positive impact on user interest, whereas perceived ease of use and security perception do not significantly affect user interest. Furthermore, the study reveals that perceived usefulness, ease of use, and security positively and significantly influence user trust. Trust mediates the relationship between perceived usefulness, ease of use, and security concerning user interest in Balipay. In practical terms, the research offers valuable insights for e-wallet service providers like Balipay, enhancing their understanding of user behavior. Service providers are also obliged to prioritize user-related interests, with the aim of increasing interest while building and maintaining a higher level of trust. Therefore, this research was conducted with the aim of providing us with an in-depth understanding of various user behaviors and providing concrete guidance for service providers to face the challenges of a larger and more dynamic market.